Dukungan Sosial Teman Sebaya Terhadap Korban Bullying - Fadilla, Rifdha; Karneli, Yeni (Current Issues in Counseling, 2023)
Cases of bullying still often occur in schools, victims of bullying come from people who are considered weak. Victims of bullying at school need to get social support from peers. Peer social support is a form of care, comfort, appreciation, or help that a person receives from another person or group. Support from peers is the most proactive way to prevent negative actions from the impact of bullying on its victims so that children who are victims of bullying do not feel alone and have the strength to fight helplessness and independence due to bullying. This study aims to describe peer social support for students who are victims of bullying in terms of aspects, namely: 1) Emotional support 2) Reward support) 3) Instrumental Support 4) Informational support) 5) Network Support. The research method used is a quantitative approach with a descriptive method. Sampling using purposive sampling technique with a total sample of 45 students of SMA Negeri 1 Hiliran Gumanti. The instrument used a peer social support questionnaire that had been tested for reliability with Cronbach's alpha of 0.947. The data analysis used is descriptive. The results of this study showed that peer social support for students victims of bullying as a whole was in the low category with a percentage of 42.22%. Furthermore, when viewed from each aspect, namely: 1) Emotional support is in the medium category with a percentage of 48.89% 2) Award support is in the low category with a percentage of 48.89% 3) Instrumental support is in the low category with a percentage of 55.56% 4) Informational support is in a low category with a percentage of 33.33% 5) Network support is in the medium category with a percentage of 42.22%. Based on the results of this study, guidance and counseling services that can be provided to improve peer social support for victims of bullying, namely information services, group counseling services and individual counseling services Keywords: Victims of Bullying, Peer Social Support